Pengaruh Price Discount, Kemudahan Pembayaran, Dan Self Control Terhadap Perilaku Impulse Buying Pada Pengguna Aplikasi Shopeefood Di Kota Surabaya Dengan Pendapatan Sebagai Variabel Moderasi - Salsabila Fairuz; Kokom Komariah; Resa Nurmala (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this study was to analyze Tourist Knowledge, on visiting decisions through tourist attitudes as a mediating variable. The population in this study were visitors to Palabuan Ratu tourism. The sample taken was 200 respondents of Palabuan Ratu tourist visitors. This study uses a Nonprobability sampling technique with Incidental Sampling type and is distributed using a google form questionnaire through Whatsapp and Instagram social media which can be accessed online by respondents with adjusted criteria. Measured by 24 indicators and using a semantic differential scale. The technical analysis used in this study was carried out using the SEM (Structural Equatio Modeling) method using the AMOS 24 application. The results of this study indicate that Tourist Knowledge (X1) has a significant effect on Visiting Decisions (Y), tourist attitudes (X2) have a significant effect on Visiting Decisions (Y), and there is an effect of tourist attitudes (X2) in mediating the relationship between Tourist Knowledge (X1) on Visiting Decisions (X2).